ANALISIS BIAYA VOLUME LABA SEBAGAI ALAT PERENCANAAN LABA PADA USAHA KOPI BUBUK CAP ANGSA KABUPATEN REJANG LEBONG - Subianto, Subianto; Chandra, Epi Lia (Jurnal AkunStie (JAS), 2021)
This study aims to determine the Cost Volume Profit Analysis as a Profit Planning Tool in Cap Angsa Powder Coffee Business, Rejang Lebong Regency. This research type is academic research and descriptive research. While the data collection method is by means of the interview method, observation method, survey method and documentation method. Based on the calculations that have been made on the data of the Cap Angsa Coffee Powder Business in Rejang Lebong Regency, it can be concluded that the break-even point for 2019 is 789 Kg. Based on the calculation of profit planning, it is known that the maximum profit that can be obtained for 2019 is IDR 108,794,161. . Based on the profit margin calculation, the percentage of sales margin of safety is 99%.